Designing, fabrication, and efficacy assessment of a new surgical guide for dental implant placement in partial edentulism - Amid, Reza; Rezaei Majd, Maryam; Javadi, Sarvin; Kadkhodazadeh, Mahdi (Journal of Dental School, 2021)
Objectives Several tools have been introduced to increase the accuracy of dental implant placement. This study aimed to design and fabricate a new surgical guide for dental implant placement in partial edentulism and assess its efficacy. Methods The designed aluminum surgical guide has eight accessories and one graded rocket. The accessories have 6, 7, 8 and 9 mm diameter, and 6 mm height. Each accessory pair has a hole for passage of 2 mm and 2.8 mm drills. The efficacy of the designed surgical guide was tested by placement of 15 dental implants in jaw models. Cone-beam computed tomography (CBCT) scans were obtained, and analyzed to assess the implant-tooth and inter-implant distances and inter-implant angulation using NNT Viewer software. Data were analyzed using one-sample t-test. P<0.05 was considered significant. Results A significant difference was noted between the planned and actual values in the implant-adjacent tooth mesiodistal distance (P<0.001), and inter-implant distance (P=0.005). However, no significant difference existed in inter-implant angulation (P=0.073). The mean implant-tooth and inter-implant distances, and the mean inter-implant angulation were 0.284±0.199 mm, 0.0350±0.176 mm, and 3.883±4.20°, respectively. Conclusion The designed surgical guide had high accuracy in achieving optimal inter-implant angulation and linear implant-adjacent tooth and inter-implant distances, and the obtained mean values were clinically acceptable.